MANAJEMEN STRATEGI PELAYANAN PADA UNIT PELAKSANA TEKNIS PENGUJIAN DAN SERTIFIKASI MUTU BARANG PROVINSI SULAWESI TENGAH - Leviana Mangopo (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study aims to determine and analyse the strategic management of services at the Technical Implementation Unit for Testing and Certification of Goods Quality in Central Sulawesi province. This research uses a qualitative approach with descriptive type. The results showed that service strategy management has been running well but not optimal. It can be seen in the aspect of strategic planning based on SWOT analysis shows that all four factors of strengths, weaknesses, opportunities, and threats are fulfilled. This shows that the strategy to improve services by UPT PSMB needs to be evaluated, updated and reformulated to be more effective and efficient in its implementation. In the aspect of implementing strategic management, there are still weaknesses, namely not optimal service, lack of promotion and socialisation, lack of facilities, limited service lines, and the use of technology that is not Up-To Date. The inhibiting factors are limited technical personnel who do not match the educational qualifications with the tasks assigned, lack of availability of standard tools used for testing and calibration, as well as limited funding and lack of motivation of the Implementation Unit personnel.